2016
DOI: 10.1007/s00240-016-0943-0
|View full text |Cite
|
Sign up to set email alerts
|

Accurate stone analysis: the impact on disease diagnosis and treatment

Abstract: This manuscript reviews the requirements for acceptable compositional analysis of kidney stones using various biophysical methods. High-resolution X-ray powder diffraction crystallography and Fourier transform infrared spectroscopy (FTIR) are the only acceptable methods in our labs for kidney stone analysis. The use of well-constructed spectral reference libraries is the basis for accurate and complete stone analysis. The literature included in this manuscript identify errors in most commercial laboratories an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 14 publications
2
23
0
Order By: Relevance
“…Up to 20% of patients with gout develop kidney stones although stone formation may also occur in patients with normal urinary and serum levels of urate (reviewed in ( 147 )). MSU crystal deposits have been detected in the renal medulla of patients with gout and furthermore renal function has been shown to be improved after successful urate-lowering treatment in gout patients (reviewed in ( 150 )). This implies that the presence of MSU crystals in the kidneys and the associated inflammation may contribute to renal insufficiency.…”
Section: Hyperuricemia and Goutmentioning
confidence: 99%
See 2 more Smart Citations
“…Up to 20% of patients with gout develop kidney stones although stone formation may also occur in patients with normal urinary and serum levels of urate (reviewed in ( 147 )). MSU crystal deposits have been detected in the renal medulla of patients with gout and furthermore renal function has been shown to be improved after successful urate-lowering treatment in gout patients (reviewed in ( 150 )). This implies that the presence of MSU crystals in the kidneys and the associated inflammation may contribute to renal insufficiency.…”
Section: Hyperuricemia and Goutmentioning
confidence: 99%
“…Over the last decade, we have seen an accumulating body of evidence which implicates gout and/or uric acid elevation as an independent predictor for hypertension, atrial fibrillation and cardiovascular disease ( 150 , 155 , 168 171 ). However, clearly not all patients with hyperuricemia go on to develop cardiovascular disease and many of those who do also exhibit one or more other established risk factors.…”
Section: Epidemiology Of Hyperuricemia and Associated Comorbiditiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Modern urological endoscopy which allows the inspection of the whole renal cavity showed that calcium oxalate and phosphate stones comprising about 80% of all concretions [8] generally start by a fixed growth on papillary calcifications, which were already described as potential source of nephrolithiasis in 1937 by Randall [9]. Recently much work was done to elucidate the pathogenesis of these calcifications being present either as interstitial deposits of calcium phosphate (Randall's plaques) or as intratubular accumulation of calcium oxalate crystals (Randall's plugs) [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the question raises whether special crystallization conditions in urine might be responsible for stone formation by the apposition of new crystals on Randall's plaques and plugs. This question stimulated us to an intensive study of the formation and especially the AGN of calcium oxalate crystals being with 60% the most frequent stone compound [8]. Experiments were directly performed in urine where like in other biological mediums, crystals as well as Randall's plaques and plugs always are coated by proteins [14].…”
Section: Introductionmentioning
confidence: 99%